Rational Metareasoning and Compilation for Optimizing Decisions Under Bounded Resources - Horvitz, Eric (2006)
Several years ago, our research group initiated a project to investigate the use of decision theory as a framework for reasoning about the design and operation of ideal agents under bounded resources.